Provision of pharmacy services to underserved populations via remote dispensing and two-way videoconferencing. - Clifton GD; Byer H; Heaton K; Haberman DJ; Gill H (American Journal of Health-System Pharmacy, 2003)
A telepharmacy program aimed to resolve the dual problem of access to prescription drugs and pharmacists for low-income populations is described. The program was conducted at the Community Health Association of Spokane (CHAS), a federally qualified community health center, and initiated in January 2001. The program, known as Telepharmacy at CHAS, allows for the dispensing of low-cost medications through participation in the federal government's 340B program and use of remote dispensing and counseling via a two-way interactive videoconferencing system to patients at six urban and rural clinics. The regulatory and practical steps necessary to implement and maintain the program are also presented. Consecutive patients whose prescriptions were filled at the base site or remote-sites were invited to complete a pharmacy satisfaction questionnaire during a two-week period in March 2003. Over the two-week period, 93 patients seen at remote sites and 106 seen at the base site completed the questionnaire. Over 75% of patients seen at the remote sites were satisfied with their videoconference interactions with the pharmacist. Of the patients seen at the base site, 66% agreed or strongly agreed that they were satisfied with the time required to obtain medications and counseling. A high percentage of patients at both the base site (94%) and remote sites (63%) strongly agreed or agreed that they would have difficulty affording their medications without this program. Telepharmacy at CHAS has been well received by most of the patients and improved their access to medications and pharmacy services.